Phenomenon of pedagogic creative work in national scientific thought - Радченко, Марина (Pedagogy of Higher and Secondary Education, 2014)
Radchenko M. V. Phenomenon of pedagogic creative work in national scientific thought. The article reviews resources for teaching creativity, dwells upon the characteristics of the phenomenon in its historical retrospection, analyzes national scientists’ views on the research problem and their contribution into pedagogic creative work as a science.